SCIENTIFIC BASIS OF CURRENT ISSUES OF EPIDEMIOLOGY - Boltayev Mirolim Muxtorovich (International Engineering Journal For Research & Development, 2020)
Substantiation of the third section of epidemiology - the epidemiology of artificial epidemic processes and other deliberately caused biological lesions (incorrect epidemiology). The article provides evidence that the epidemiology, etiology and clinic of natural and artificially caused epidemics (outbreaks) and other massive artificial injuries of the population of biological nature have fundamental differences. And if the artificial nature of the epidemic (outbreak) of an infectious disease is not revealed in a timely manner, then attempts to interrupt it by influencing the links of the classical triad of the epidemic process will be ineffective.